Prosthetic rehabilitation, failures and their causes - Yulemy Portal García; Anabel Zurbano Cobas; María Gabriela Pérez Cuevas; Lorena Camacho Guerrero; Lisbet Pineda Bombino; Dairon Aguilar Valdez (Acta Médica del Centro)
Introduction: The identification of factors that contribute to the failure of prosthetic rehabilitations is crucial to improve the clinical results and quality of life of patients. Objective: To describe the causes of prosthetic rehabilitation failures in patients treated in the Prosthetics Service at Arnaldo Milián Castro Hospital from January 2019 to March 2020. Methods: A descriptive cross-sectional study was carried out in a sample (547) selected by criteria. Document analysis of the medical records was used and the variables were worked on: the result of the rehabilitation (success/failure), sex, age group, type of prosthesis and causes of failure. Results: Of the total units of analysis (918), there were 825 (89.87%) successes and 93 (10.13%) failures. From these latter, 17 were due to functional clinical errors, 9were due to aesthetic and 74 were due to laboratory errors. By sex, there were 2 women with failure for every man; By age, older adults prevailed. The aesthetic errors causes related to the teeth and the plane in partial and total upper prostheses were common. In the functional ones, non-compliance with biomechanical principles and defective centric relation in lower total prosthesis were important. In the laboratory, packaging errors, fractures and lack of packaging material prevailed. Conclusions: The frequency of errors in patients with prosthetic rehabilitation indicates the need for continuous evaluation in order to achieve patient satisfaction.